It Takes Three Receptors to Raise a B Cell. Issue 7 (July 2020) - McLean, Kaitlin C.; Mandal, Malay
Abstract : As the unique source of diverse immunoglobulin repertoires, B lymphocytes are an indispensable part of humoral immunity. B cell progenitors progress through sequential and mutually exclusive states of proliferation and recombination, coordinated by cytokines and chemokines. Mutations affecting the crucial pre-B cell checkpoint result in immunodeficiency, autoimmunity, and leukemia. This checkpoint was previously modeled by the signaling of two opposing receptors, IL-7R and the pre-BCR. We provide an update to this model in which three receptors, IL-7R, pre-BCR, and CXCR4, work in concert to coordinate both the proper positioning of B cell progenitors in the bone marrow (BM) microenvironment and their progression through the pre-B checkpoint. Furthermore, signaling initiated by all three receptors directly instructs cell fate and developmental progression. Highlights: The generation of a diverse antibody repertoire is crucial for the adaptive immune system and is accomplished through sequential V(D)J recombination of loci encoding the immunoglobulin heavy (IgH) and light chain (Igκ and Igλ). The tight regulation and separation of proliferation and differentiation processes during B cell development is crucial for avoiding genomic instability. Previous models identified two receptors, IL-7R and the pre-BCR, as being essential in the regulation of the pre-B cell checkpoint. However, new research has brought to light the crucial role of a third receptor, CXCR4, in mouse models. CXCR4 drives the positioning of developing B cells within specific microniches in the murine BM. CXCR4 then mediates a feed-forward loop initiated by the pre-BCR that coordinates cell-cycle exit and pre-BCR repression. CXCR4 is also crucial for Igκ recombination and for inducing the pathways to recruit the required transcription factors and chromatin remodeling complexes.